ANALISIS MANAJEMEN RISIKO DALAM MENINGKATKAN KUALITAS PELAYANAN UMRAH PADA PT SINAI TOUR AND TRAVEL UMRAH DAN HAJI PLUS BUKITTINGGI - Uswatul Hasana; Yenti Astarie Dewi (BORJUIS: JURNAL OF ECONOMY, 2025)
This study is based on the high public interest in the Hajj and Umrah pilgrimages, which has resulted in increased demand for travel services. To maintain service quality and customer satisfaction, risk management is very important, especially when we face problems such as hotel price fluctuations, changes in flight schedules, and competition between travel agents. The purpose of this research is to see how the application of risk management can improve the quality of service at PT. Sinai Tour & Travel Umrah and Hajj Plus Bukittinggi. In addition, this research aims to provide recommendations on how companies can manage risks that can affect the satisfaction of community members. Analysis of descriptive data and information about risk management and quality of services used. It is hoped that this research can help develop risk management theory and practice in the Hajj and Umrah travel industry because the results show that service quality can be improved with good risk management practices.